EFFECT OF RAW AND PROCESSED OAT BRAN ON LIPID PROFILE OF NORMAL, HYPERCHOLESTEROLEMIC AND DIABETIC RATS - M. A. Khan; F. M. Anjum; I. Pasha; M. Nadeem; M. A. Sheikh (Journal of Animal and Plant Sciences, 2014)
The core objective of current research is to explore the functional properties of diets containing raw and processed oat bran to combat lifestyle disorders i.e. cardiovascular diseases. For the purpose, raw oat bran was procured from Ayub Agricultural Research Institute (AARI), Faisalabad and it was processed through extrusion technique. In addition, three types of studies were conducted on the basis of diets i.e. study I (normal rats), study II (hypercholesterolemic rats) and study III (diabetic rats). Moreover, the efficacy study was carried out to observe the effects of different levels of raw and processed oat bran on biological profile of blood Sprauge-Dawley rats. Results showed that the cholesterol, LDL and triglycerides level reduction was found significantly different when raw and processed oat bran diets fed to normal, hypercholesterolemic and diabetic rats. The highest reduction was recorded when fed on diet containing 30% processed oat bran. The processed oat bran exhibited more reduction as compared to raw oat bran. Conclusively, it is suggested that processed oat bran should be introduced in diet based therapy to control lifestyle-related disorders.
Keywords: Oat bran; β-glucan; cholesterol; LDL; triglycerides